Advances in Understanding the Molecular Mechanisms and Potential Genetic Improvement for Nitrogen Use Efficiency in Barley - Sakura D. Karunarathne; Yong Han; Xiao-Qi Zhang; Chengdao Li (Agronomy, 2020)
Nitrogen (N) fertilization plays an important role in crop production; however, excessive and inefficient use of N fertilizer is a global issue that incurs high production costs, pollutes the environment and increases the emission of greenhouse gases. To overcome these negative consequences, improving nitrogen use efficiency (NUE) would be a key factor for profitable crop production either by increasing yield or reducing fertilizer cost. In contrast to soil and crop management practices, understanding the molecular mechanisms in NUE and developing new varieties with improved NUE is more environmentally and economically friendly. In this review, we highlight the recent progress in understanding and improving nitrogen use efficiency in barley, with perspectives on the impact of N on plant morphology and agronomic performance, NUE and its components such as N uptake and utilization, QTLs and candidate genes controlling NUE, and new strategies for NUE improvement.